Identification in Cognitive Maps in Impulse Process Mode with Incomplete Measurement of Nodes Coordinates - Miliavskyi, Yu.L. (Кибернетика и вычислительная техника, 2019)
The purpose of the article is to research and develop a method for identifying weights of cognitive map nodes in case when number of nodes is known, but not all of them are measured. Results. Identification method based on 4SID method is suggested. It allows finding some realization of the system equivalent to the original cognitive map in its outputs, with the control observation matrices remaining unchanged. Invariants of the original and identified systems are analyzed. Practical example of identifying a cognitive map of an IT company is considered. It is shown what the accuracy of the suggested method depends on and under which conditions it is applicable. Метою статті є розроблення і дослідження методу ідентифікації вагових коефіцієнтів ребер когнітивної карти у випадку, коли кількість вершин карти відома, але не усі з них вимірюються. Результати. Запропоновано метод ідентифікації, що базується на 4SID методі (методі виділеного підпростору). Цей метод дає змогу знайти деяку реалізацію системи, еквівалентну за виходом з початковою когнітивною картою, водночас матриці керування та спостереження залишаються без змін. Проаналізовано інваріанти вихідної та ідентифікованої систем. Розглянуто практичний приклад ідентифікації когнітивної карти IT компанії. Показано, від чого залежить точність запропонованого методу та за яких умов його можна застосовувати. Исследована задача идентификации весовых коэффициентов матриц смежности когнитивных карт в случае, когда часть координат вершин не измеряется. Предложен метод идентификации, основывающийся на 4SID методе. Проанализированы инварианты исходной и идентифицированной систем. Рассмотрен практический пример идентификации когнитивной карты IT компании. Показано, при каких условиях предложенный метод применим.